Anti-icing fan blade coating suitable for high and cold areas and process of anti-icing fan blade coating
By applying a coating process containing components such as ceramic matrix composite materials, shape memory alloy particles, thermally responding polymers, photocatalyst titanium dioxide, etc. on fan blades in high-altitude areas, the problem of snow and freezing of fan blades in low temperature and high wind speed environments is solved, and the coating is efficiently anti-icing, self-cleaning, corrosion resistance and wear resistance is achieved, and the operation stability and service life of the fan are significantly improved.
Patent Information
- Application Number
- CN202411806997.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Fan blades in high-altitude areas are prone to snow and freezing in low temperatures, high wind speeds and heavy snow, resulting in a lot of ice and snow attached to the surface of the blades, affecting the fan efficiency and even causing shutdown or damage. Existing coating technology has shortcomings in terms of durability, self-cleaning ability, corrosion resistance and wear resistance.
A coating process including ceramic matrix composite material, shape memory alloy particles, thermally responsive polymers, photocatalyst titanium dioxide, superhydrophobic nanoparticles, antioxidant enhancers, fluoride composite materials, and solvents and diluents is adopted. The coating improves anti-icing and self-cleaning performance through the combination of shape memory alloy particles and thermally responsive polymers; enhances the self-cleaning function through the introduction of photocatalyst titanium dioxide; and ceramic-based composite materials and fluoride composite materials improve the corrosion resistance and wear resistance of the coating.
This coating effectively reduces the adhesion of ice and snow, improves the anti-ice accumulation ability of fan blades, significantly improves the long-term stability and working efficiency of the coating, reduces the frequency of manual cleaning and maintenance costs, and extends the service life and reliability of fan blades.
Smart Images

Figure CN119570298A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coatings, and in particular to a coating and a process thereof for preventing ice-covering of wind turbine blades in high-cold areas. Background Art
[0002] In high-altitude cold regions, wind power generation has gradually become an important form of energy. However, extreme weather conditions such as severe cold, ice and snow cover have brought great challenges to the stable operation of wind power generation equipment. In particular, wind turbine blades, as the most critical components of wind power generation systems, are easily snowed and iced when exposed to low temperatures, high wind speeds and heavy snow for a long time, resulting in a large amount of ice and snow attached to the surface of the blades, which in turn affects the efficiency of the wind turbine and even causes shutdown or damage. Therefore, how to effectively prevent ice, corrosion and wear of wind turbine blades has become a key issue in the research of wind power technology in high-altitude cold regions.
[0003] At present, the anti-icing technology of wind turbine blades mainly relies on anti-icing coating. Traditional anti-icing coating technology is mainly based on physical deicing, electric heating deicing and coating anti-icing. Coating anti-icing has gradually become a research hotspot due to its low cost, no moving parts and maintenance-free characteristics. However, the existing coating technology generally has the following shortcomings: First, the durability of the coating is poor, especially in the high-cold wind and sand environment. After long-term use, the coating surface is prone to aging, falling off or wear, resulting in a weakened anti-icing effect; second, the existing coating has insufficient self-cleaning ability and cannot effectively remove pollutants accumulated on the blade surface, such as sand or bird droppings; finally, the corrosion resistance and wear resistance of the coating are weak, and it is difficult to adapt to the complex changes in the environment of high-cold areas.
[0004] Therefore, there is an urgent need for a new coating technology that can ensure anti-icing performance while also having multiple properties such as self-cleaning, corrosion resistance, and wear resistance, so as to adapt to the complex environmental conditions in high-cold areas. To this end, the present invention proposes an anti-icing fan blade coating and its process suitable for high-cold areas. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a coating and process for anti-icing wind turbine blades in high-cold areas, which solves the problems of insufficient anti-icing, corrosion resistance, wear resistance and self-cleaning performance of wind turbine blades in high-cold areas.
[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: a coating for anti-icing fan blades suitable for high-cold areas, comprising the following components by weight percentage:
[0007] 45-55% ceramic matrix composites, which include aluminum oxide, silicon nitride and silicon carbide;
[0008] 5-10% shape memory alloy particles;
[0009] 2-5% thermoresponsive polymer;
[0010] 3-7% photocatalyst titanium dioxide;
[0011] 5-8% superhydrophobic nanoparticles;
[0012] 10-15% antioxidant enhancer;
[0013] 5-8% fluoride composites;
[0014] 10-15% solvents and thinners.
[0015] Preferably, the shape memory alloy particles are selected from one of nickel-titanium alloy and copper-based shape memory alloy, and the thermal responsive polymer is a polymer shape memory polymer.
[0016] Preferably, the super-hydrophobic nanoparticles are selected from one of silicon fluoride nanoparticles and carbon fluoride nanoparticles, and the antioxidant enhancer is selected from one of titanium alloy particles and aluminum alloy particles.
[0017] Preferably, the fluoride composite material is selected from one of aluminum fluoride and sodium fluoride, and the solvent and diluent is selected from one of ethanol, isopropanol, xylene and ammonium acetate.
[0018] Preferably, the particle size range of the ceramic-based composite material is 1-10 μm, and the mixing ratio of the ceramic-based composite material is aluminum oxide: silicon nitride: silicon carbide = 3:2:1.
[0019] Preferably, the particle size of the shape memory alloy particles is in the range of 20-50 μm, the particle size of the super hydrophobic nanoparticles is in the range of 10-100 nm, and the particle size of the antioxidant enhancer is in the range of 10-50 μm.
[0020] A coating process for wind turbine blades against ice in high-cold areas, which is used to prepare the coating for wind turbine blades against ice in high-cold areas using the above-mentioned component materials, comprises the following steps:
[0021] S1. Material preparation: preparing the component materials according to the above weight percentage, including ceramic-based composite materials, shape memory alloy particles, thermal responsive polymers, photocatalysts, super-hydrophobic nanoparticles, antioxidant enhancers, fluoride composite materials and solvents;
[0022] S2. Material mixing and homogenization: The above components are put into a mixing container according to a predetermined ratio, and are preliminarily mixed by a biaxial high-speed stirrer, with the stirring speed set to 500-800 rpm for 15 min. Thereafter, they are further mixed by a ball mill, and wet ball milling is performed using isopropanol or ethanol as a solvent;
[0023] S3, solvent addition: adding solvent and diluent according to the required viscosity requirements of the coating liquid;
[0024] S4, coating operation: using a spraying device, the coating liquid uniformly mixed in the above steps is evenly coated on the surface of the fan blade;
[0025] S5. Curing and drying: Perform preliminary curing at 40°C-80°C for 10-20 minutes, then raise the temperature to 120°C for 20-40 minutes of high temperature curing, and finally allow the coating to cool naturally at room temperature;
[0026] S6. Surface treatment: Use corona treatment technology to enhance the coating surface, the power is set to 2-4kV, the treatment time is 1-2min, and the surface is scanned by laser beam, the laser power is set to 50-150W, and the scanning speed is 5-10mm / s
[0027] Preferably, the viscosity of the coating liquid in step S3 is in the range of 50-100 cP.
[0028] Preferably, when the coating operation in step S4 is performed by spraying, the spraying pressure of the spraying equipment is 0.2-0.5 MPa, and the spraying distance is controlled within the range of 10-15 cm.
[0029] The present invention provides a wind turbine blade coating and process suitable for anti-icing in high-cold areas. It has the following beneficial effects:
[0030] 1. The present invention improves the anti-icing and self-cleaning performance of the coating by combining shape memory alloy particles with thermal responsive polymers. In high-cold areas, ice often accumulates on the surface of fan blades due to low temperature, which seriously affects the normal operation of the fan. Shape memory alloy particles change shape at low temperatures and can help remove attached ice and snow through physical changes. The introduction of thermal responsive polymers makes the coating adaptive under temperature changes and can actively adjust the surface properties within a certain temperature range, making the coating surface smoother and helping to accelerate the sliding of ice and snow. The synergistic effect of the two not only effectively reduces the adhesion of ice and snow, but also greatly improves the ability of fan blades to resist ice accumulation.
[0031] 2. The present invention introduces the photocatalyst titanium dioxide. The application of this material in the coating greatly enhances the self-cleaning function of the coating. Titanium dioxide has excellent photocatalytic properties, can decompose organic pollutants, oil pollution, microorganisms, etc. under ultraviolet irradiation, and has anti-pollution ability. In high-cold areas, wind turbine blades not only face the challenge of ice and snow cover, but are often troubled by pollutants. The photocatalytic effect of titanium dioxide can promote the degradation and removal of pollutants, keep the surface of the blades clean, and reduce the frequency of manual cleaning and maintenance costs. At the same time, the introduction of this function significantly improves the long-term stability and work efficiency of the coating, especially in cold and harsh environments, solves the problem of dirt accumulation on wind turbine blades under harsh weather conditions, and improves the service life and reliability of the fan. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Flow chart of the process of the present invention. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Please refer to the attached Figure 1 The embodiment of the present invention provides a wind turbine blade coating suitable for anti-icing in high-cold areas, which includes the following components by weight percentage:
[0035] 45-55% ceramic matrix composites, which include aluminum oxide, silicon nitride and silicon carbide;
[0036] 5-10% shape memory alloy particles;
[0037] 2-5% thermoresponsive polymer;
[0038] 3-7% photocatalyst titanium dioxide;
[0039] 5-8% superhydrophobic nanoparticles;
[0040] 10-15% antioxidant enhancer;
[0041] 5-8% fluoride composites;
[0042] 10-15% solvents and thinners.
[0043] Specifically, in this embodiment, the addition of ceramic-based composite materials is mainly aimed at enhancing the hardness and wear resistance of the coating, improving the corrosion resistance of the coating, and reducing the adhesion of ice and snow on the surface of the wind turbine blades. The combination of ceramic-based composite materials includes three materials: aluminum oxide, silicon nitride, and silicon carbide. Aluminum oxide mainly provides excellent wear resistance and corrosion resistance; silicon nitride provides higher thermal stability and mechanical strength; silicon carbide effectively improves the hardness and anti-friction ability of the coating, thereby enhancing the coating's resistance to wind, sand, ice and snow. Ceramic-based composite materials can not only improve the coating's anti-icing ability, but also significantly improve the durability of the coating, reducing the frequent maintenance of wind turbine blades due to icing.
[0044] In this embodiment, shape memory alloy particles (such as nickel-titanium alloy or copper-based alloy) are added to the coating as a high-performance smart material, which can respond to temperature changes and achieve self-repair function through shape changes. Specifically, the shape memory alloy particles can automatically restore their original shape when the ambient temperature changes. For example, when tiny cracks appear on the coating surface due to ice, the shape memory alloy particles will return to their initial shape when the temperature rises, thereby repairing these cracks and avoiding damage or shedding of the coating due to ice and snow accumulation.
[0045] The thermally responsive polymer in this embodiment can respond to temperature changes and change its physical properties. The polymer achieves an anti-icing function by changing its surface state in a low-temperature environment to reduce the adhesion of ice and snow. The surface of the polymer will further improve its fluidity when the temperature rises, so that the iced area can be cleared and the efficient operation of the fan blades can be maintained. At the same time, the addition of the thermally responsive polymer also improves the low-temperature resistance of the coating, and has better adaptability in extremely cold environments.
[0046] Titanium dioxide, as a photocatalyst, can produce oxygen free radicals and other active substances under ultraviolet light, playing a self-cleaning role. For dust, oil, pollutants, etc. that may accumulate on the surface of wind turbine blades, the photocatalytic effect of titanium dioxide can effectively decompose these pollutants and prevent them from accumulating on the surface of blades for a long time. By reducing the adhesion of pollutants, the surface of the coating is smoother, avoiding the impact of dirt on the aerodynamic performance of the blades. This feature can reduce the number of cleaning times and reduce operation and maintenance costs during the long-term operation of wind turbine blades.
[0047] In this embodiment, super-hydrophobic nanoparticles (such as silicon fluoride or carbon fluoride nanoparticles) give the coating extremely strong hydrophobic properties. The super-hydrophobic coating can effectively reduce the adhesion of liquid substances such as water droplets, ice and snow, so that the wind turbine blades can quickly slide off in snowy and icy environments, avoiding the accumulation of ice and snow, thereby reducing the risk of wind turbine shutdown due to icing. Super-hydrophobic materials can reduce the adhesion of ice and snow and help the blades maintain good aerodynamic properties.
[0048] The antioxidant enhancer in this embodiment, such as titanium alloy particles or aluminum alloy particles, can significantly improve the antioxidant performance of the coating. When wind turbine blades are operating in high-altitude cold areas, they usually need to withstand extreme temperature changes and oxidative environments. The antioxidant enhancer can effectively prevent the coating from oxidizing in high temperature or extremely cold environments, ensuring the stability and service life of the coating.
[0049] In this embodiment, the fluoride composite material, such as aluminum fluoride and sodium fluoride, mainly plays an anti-corrosion role. When the fan blades are exposed to low temperature and humid environment, they are often corroded by salt spray and chemicals. The addition of fluoride composite material significantly improves the corrosion resistance of the coating, prolongs the service life of the coating, and ensures the stability of the fan blades in harsh environments.
[0050] In this embodiment, the main function of the solvent and diluent (such as ethanol, isopropanol, xylene, etc.) is to adjust the viscosity of the coating liquid to ensure the uniformity and good adhesion of the coating liquid during the coating process. The selection of the solvent can help control the fluidity of the coating liquid so that the coating is evenly coated on the surface of the wind turbine blade, avoiding uneven or incomplete coating.
[0051] The shape memory alloy particles are selected from one of nickel-titanium alloy and copper-based shape memory alloy, and the thermal response polymer is a polymer shape memory polymer.
[0052] The super hydrophobic nanoparticles are selected from one of silicon fluoride nanoparticles and carbon fluoride nanoparticles, and the antioxidant enhancer is selected from one of titanium alloy particles and aluminum alloy particles.
[0053] The fluoride composite material is selected from one of aluminum fluoride and sodium fluoride, and the solvent and diluent is selected from one of ethanol, isopropanol, xylene and ammonium acetate.
[0054] The particle size range of the ceramic matrix composite material is 1-10 μm, and the mixing ratio of the ceramic matrix composite material is aluminum oxide: silicon nitride: silicon carbide = 3:2:1.
[0055] The particle size of the shape memory alloy particles ranges from 20 to 50 μm, the particle size of the super hydrophobic nanoparticles ranges from 10 to 100 nm, and the particle size of the antioxidant enhancer ranges from 10 to 50 μm.
[0056] A coating process for anti-icing wind turbine blades in high-cold areas is used for preparing a component material, comprising the following steps:
[0057] S1. Material preparation: preparing the component materials according to the above weight percentage, including ceramic-based composite materials, shape memory alloy particles, thermal responsive polymers, photocatalysts, super-hydrophobic nanoparticles, antioxidant enhancers, fluoride composite materials and solvents;
[0058] S2. Material mixing and homogenization: The above components are put into a mixing container according to a predetermined ratio, and are preliminarily mixed by a biaxial high-speed stirrer, with the stirring speed set to 500-800 rpm for 15 min. Thereafter, they are further mixed by a ball mill, and wet ball milling is performed using isopropanol or ethanol as a solvent;
[0059] S3, solvent addition: adding solvent and diluent according to the required viscosity requirements of the coating liquid;
[0060] S4, coating operation: using a spraying device, the coating liquid uniformly mixed in the above steps is evenly coated on the surface of the fan blade;
[0061] S5. Curing and drying: Perform preliminary curing at 40°C-80°C for 10-20 minutes, then raise the temperature to 120°C for 20-40 minutes of high temperature curing, and finally allow the coating to cool naturally at room temperature;
[0062] S6. Surface treatment: Use corona treatment technology to enhance the coating surface, the power is set to 2-4kV, the treatment time is 1-2min, and the surface is scanned by laser beam, the laser power is set to 50-150W, and the scanning speed is 5-10mm / s.
[0063] The viscosity of the coating liquid in step S3 is in the range of 50-100 cP.
[0064] When the coating operation in step S4 is performed by spraying, the spraying pressure of the spraying equipment is 0.2-0.5 MPa, and the spraying distance is controlled within the range of 10-15 cm.
[0065] Embodiment 1:
[0066] Overview of steps:
[0067] Materials preparation:
[0068] Ceramic matrix composite material: aluminum oxide (45%), silicon nitride (35%), silicon carbide (20%), particle size is 1-10 μm.
[0069] Shape memory alloy particles: nickel-titanium alloy, with a particle size range of 20-50μm, accounting for 7%.
[0070] Thermoresponsive polymers: polymer shape memory polymers, accounting for 3%.
[0071] Photocatalyst: Titanium dioxide, accounting for 5%.
[0072] Super hydrophobic nanoparticles: Silicon fluoride nanoparticles, accounting for 6%, with a particle size of 20-50nm.
[0073] Antioxidant enhancer: aluminum alloy particles, accounting for 12%, with a particle size of 10-50μm.
[0074] Fluoride composite materials: aluminum fluoride, accounting for 6%.
[0075] Solvents and thinners: Isopropyl alcohol, 15%.
[0076] Material mixing and homogenization: In a biaxial high-speed stirrer, the stirring speed was set to 600 rpm for 15 min, and then wet ball milling was performed using isopropanol as the solvent for 1 h.
[0077] Solvent addition: According to the target viscosity requirement, add isopropyl alcohol as solvent and adjust the viscosity to 90 cP.
[0078] Coating operation: Use spraying equipment, set the spraying pressure to 0.3MPa, the spraying distance to 12cm, and evenly apply to the surface of the fan blades.
[0079] Curing and drying:
[0080] Initial curing: Dry at 40°C for 10 minutes.
[0081] High temperature curing: The temperature was then raised to 120°C for 30 minutes of curing, and finally cooled naturally at room temperature.
[0082] Surface treatment:
[0083] Corona treatment was used with a power setting of 3 kV and a treatment time of 1.5 min to ensure that the coating surface had excellent adhesion.
[0084] Laser beam scanning: laser power is 100W and scanning speed is 7mm / s.
[0085] Summary of Example 1: Example 1 provides a standard coating preparation scheme, which is suitable for anti-icing wind turbine blades in high-cold areas. The technical solution of this embodiment focuses on the basic coating composition and treatment process, and achieves anti-icing and anti-corrosion effects by rationally selecting ingredients such as ceramic-based composite materials, shape memory alloy particles and super-hydrophobic nanoparticles. Its specific coating formula and production steps provide a solid foundation for the performance of the coating, which can effectively cope with the harsh environment of high-cold areas. Through spraying, curing and drying, and corona treatment, the coating exhibits good adhesion, corrosion resistance, and excellent anti-icing effect, which is suitable for conventional high-cold wind turbine blade protection applications.
[0086] Embodiment 2:
[0087] Overview of steps:
[0088] Materials preparation:
[0089] Ceramic-based composite material: aluminum oxide (50%), silicon nitride (30%), silicon carbide (20%), with a particle size of 1-10 μm, optimizing the ratio of aluminum oxide to silicon nitride and enhancing the heat resistance and hardness of the coating.
[0090] Shape memory alloy particles: copper-based shape memory alloy, with a particle size range of 20-40μm, accounting for 8%, which improves the reactivity of the shape memory alloy.
[0091] Thermoresponsive polymers: polymer shape memory polymers, accounting for 4%.
[0092] Photocatalyst: Titanium dioxide, accounting for 4%, reduces the content of photocatalyst and improves the flexibility of the overall coating.
[0093] Super hydrophobic nanoparticles: Fluorinated carbon nanoparticles, accounting for 6%, with a particle size of 10-20nm, optimize the super hydrophobic effect.
[0094] Antioxidation enhancer: Titanium alloy particles, accounting for 13%, with a particle size of 20-50μm, increase the corrosion resistance of the coating.
[0095] Fluoride composite material: Sodium fluoride, accounting for 6%, further optimizes the anti-icing effect of the coating.
[0096] Solvents and diluents: ethanol, accounting for 12%.
[0097] Material mixing and homogenization: In a biaxial high-speed stirrer, the stirring speed was set to 650 rpm for 20 min, followed by wet ball milling using ethanol as the solvent for 1.5 h.
[0098] Solvent addition: The solvent viscosity was adjusted to 75 cP, and ethanol was used as the solvent to increase the fluidity of the coating.
[0099] Coating operation: Use spraying equipment with a spraying pressure of 0.4MPa and a spraying distance of 10cm to ensure that the coating evenly covers the surface of the fan blades.
[0100] Curing and drying:
[0101] Initial curing: Dry at 60°C for 15 minutes.
[0102] High temperature curing: The temperature was then raised to 125°C for 35 minutes of curing, and finally cooled naturally at room temperature.
[0103] Surface treatment: Corona treatment was used with a power setting of 3.5 kV and a treatment time of 1.5 min.
[0104] Laser beam scanning: laser power is 120W and scanning speed is 6mm / s.
[0105] Example 2 Summary: Example 2, based on Example 1, optimizes the composition and process of the coating, further improving the performance of anti-icing, heat resistance, and super-hydrophobicity. By adjusting the proportion of ceramic-based composite materials (increasing the specific gravity of aluminum oxide), selecting different shape memory alloys (copper-based shape memory alloys), and optimizing the type and proportion of super-hydrophobic nanoparticles, the responsiveness and functionality of the coating are improved. In addition, a more suitable solvent (ethanol) and diluent are used to adjust the viscosity of the coating liquid to ensure the uniformity of the coating operation. These improvements make the performance of the coating more stable in a high-cold environment, and improve the adhesion and durability of the coating. The technical solution of this embodiment is applicable to those fan blades that need to operate efficiently in extreme climates, ensuring a longer anti-icing effect and higher performance reliability.
[0106] Embodiment 3:
[0107] Overview of steps:
[0108] Materials preparation:
[0109] Ceramic matrix composite material: Alumina (55%), silicon nitride (25%), silicon carbide (20%), particle size 1-10μm, with a higher proportion of alumina to improve heat resistance and mechanical strength.
[0110] Shape memory alloy particles: nickel-titanium alloy, with a particle size range of 20-40 μm, accounting for 9%, further improving the activity of the shape memory alloy.
[0111] Thermoresponsive polymers: polymer shape memory polymers, accounting for 5%.
[0112] Photocatalyst: Titanium dioxide, accounting for 5%, improves the self-cleaning function of the coating.
[0113] Super hydrophobic nanoparticles: Fluorinated carbon nanoparticles, accounting for 8%, with a particle size of 5-10nm, optimize super hydrophobicity.
[0114] Antioxidation enhancer: Aluminum alloy particles, accounting for 10%, with a particle size of 30-50μm, to enhance corrosion resistance.
[0115] Fluoride composite material: Aluminum fluoride, accounting for 5%, enhances the anti-icing effect.
[0116] Solvents and diluents: Xylene, accounting for 10%, increases the fluidity and uniformity of the coating.
[0117] Material mixing and homogenization: In a biaxial high-speed stirrer, the stirring speed was set to 700 rpm, the stirring time was 25 min, and xylene was used as the solvent for wet ball milling for 2 h.
[0118] Solvent addition: The solvent viscosity is adjusted to 80 cP, and xylene is used as the solvent to ensure that the coating has good fluidity during the spraying process.
[0119] Coating operation: Use spraying equipment with a spraying pressure of 0.5MPa and a spraying distance of 8cm to ensure that the coating is uniform and fully covers the surface of the fan blades.
[0120] Curing and drying:
[0121] Initial curing: Dry at 70°C for 20 minutes.
[0122] High temperature curing: The temperature was then raised to 130°C for 40 minutes of curing, and finally cooled naturally at room temperature.
[0123] Surface treatment:
[0124] Corona treatment was used with a power setting of 4 kV and a treatment time of 2 min to further enhance the adhesion of the coating surface.
[0125] Laser beam scanning: laser power is 150W and scanning speed is 5mm / s.
[0126] Summary of Example 3: Based on Example 2, Example 3 further innovates the composition and process of the coating, especially in terms of the anti-icing, anti-corrosion and mechanical properties of the coating. The responsiveness, hydrophobicity and corrosion resistance of the coating are improved by further increasing the proportion of aluminum oxide (reaching 55%), optimizing the particle size distribution of shape memory alloy particles (using nickel-titanium alloy), and using super-hydrophobic carbon fluoride nanoparticles. In addition, xylene was selected as a solvent to further optimize the fluidity of the coating liquid and ensure uniform coverage of the coating during the spraying process. During the curing and drying process, higher temperatures and longer times were used to make the coating more stable and enhance its ability to resist environmental changes. Finally, laser beam scanning processing further improves the surface quality and adhesion of the coating, making its application in high-cold areas more reliable. The technical solution of this embodiment is suitable for wind turbine blades with higher requirements for anti-icing effects in extremely cold environments, ensuring its excellent performance and durability in long-term harsh environments.
[0127] Summary: From Example 1 to Example 3, the key properties of the coating, such as anti-icing, anti-corrosion, high temperature resistance, super hydrophobicity and adhesion, are gradually improved. Example 1 is a basic technical solution, which ensures that the coating has basic anti-icing effect and adhesion in high-cold areas; Example 2 further improves the functionality and stability of the coating by optimizing the coating formula and adjusting the use of solvents and diluents; and Example 3, based on the previous two, further enhances the various properties of the coating, especially anti-icing, corrosion resistance and hydrophobicity, making it suitable for more severe extreme cold environments. Each example has carried out technical innovation and optimization on the basis of the previous example, ensuring the anti-icing effect and long-term reliability of wind turbine blades in high-cold areas.
[0128] Performance test experiment: Anti-icing wind turbine blade coating performance evaluation experiment
[0129] 1. Purpose of the experiment
[0130] The main purpose of this experiment is to evaluate the comprehensive anti-icing, adhesion, corrosion resistance, wear resistance, thermal stability and other properties of the coatings prepared in Examples 1, 2 and 3 in a simulated high-cold environment. Through a comprehensive evaluation of the coating performance, its adaptability and reliability in applications in high-cold areas are further verified, and an experimental basis is provided for the optimization of the anti-icing coating of wind turbine blades.
[0131] 2. Experimental Equipment
[0132] Ice and snow adhesion tester (measures the ice and snow adhesion of coatings)
[0133] Salt spray corrosion test chamber (simulated corrosive environment)
[0134] Friction and wear tester (testing the wear resistance of coating)
[0135] Low temperature environment simulation box (simulating high cold environment)
[0136] Thermal stability tester (test thermal stability of coating, thermal gravimetric analysis)
[0137] Mechanical fatigue testing machine (tests the durability of coatings under mechanical fatigue)
[0138] Scanning electron microscopy (SEM) (analysis of coating surface microstructure and damage)
[0139] 3. Experimental Materials
[0140] Samples: coatings prepared in Example 1, Example 2 and Example 3.
[0141] Substrate: Standard wind turbine blade (substrate for coating application).
[0142] 4. Experimental steps (1) Ice and snow adhesion test
[0143] Purpose: To test the anti-icing adhesion of coatings in high-cold environments and evaluate the anti-icing effect of coatings.
[0144] step:
[0145] The coating samples were placed in a low-temperature environment simulation box with the temperature set at -20°C to simulate actual cold weather conditions.
[0146] Start the ice and snow adhesion tester, and use the automated system to evenly adhere a layer of artificial snow or ice and snow simulation material to the coating surface.
[0147] The pressure is gradually increased through the pressure loading system, the maximum value of the ice and snow adhesion (unit: N) is measured and recorded, and the presence of ice peeling or cracking on the sample surface is observed.
[0148] (2) Salt spray corrosion test
[0149] Purpose: To test the corrosion resistance of coatings in salt spray environment and simulate the long-term performance of fan blades in high humidity and high salt environment.
[0150] step:
[0151] The coating samples were placed in a salt spray corrosion test chamber, the salt spray concentration was set to 5% NaCl solution, the test chamber temperature was maintained at 35°C, and the relative humidity was 95% RH.
[0152] Conduct a 48-hour salt spray corrosion test and regularly check the corrosion condition of the coating.
[0153] The corrosion area of the coating was analyzed by visual inspection and electron microscopy, and the integrity of the coating (coating peeling ratio) was recorded.
[0154] (3) Wear resistance test
[0155] Purpose: To evaluate the wear resistance of coatings under the action of wind and sand and mechanical friction in high-altitude cold areas and to test their durability under harsh conditions.
[0156] step:
[0157] The friction test was carried out using a friction and wear tester, with the friction load set to 10N and the friction medium to quartz sand (particle size 100 μm).
[0158] Set the friction time to 1 h and record the wear amount periodically.
[0159] After the test, the wear depth and damage of the coating surface were analyzed by surface morphology observation (using SEM scanning electron microscope).
[0160] (4) Thermal stability test
[0161] Purpose: To test the thermal stability of coatings in high temperature environments and to evaluate the performance changes of coatings after temperature changes in high-cold environments.
[0162] step:
[0163] The thermal stability of the coating was tested using a thermogravimetric analyzer (TGA). The sample was heated to 500°C with a heating rate of 10°C / min.
[0164] Record the thermal weight loss curve of the coating and measure the maximum thermal weight loss temperature and temperature range of the coating.
[0165] Based on the results of thermogravimetric analysis, the thermal stability of the coating and the influence of temperature changes on its physicochemical properties were evaluated.
[0166] (5) Mechanical fatigue test
[0167] Purpose: To test the fatigue performance of coatings under long-term vibration or pressure cycling of wind turbine blades and evaluate their durability under long-term mechanical loads.
[0168] step:
[0169] Use a mechanical fatigue tester to simulate the vibration load of the fan blades under the action of wind force. Set the vibration frequency to 10Hz and the cyclic load amplitude to 50-100N.
[0170] Perform a minimum of 50,000 cycles and regularly observe the coating for cracking, peeling, or significant wear.
[0171] The fatigue life of the coating was measured and the microstructural changes on the coating surface were observed.
[0172] 5. Experimental Design
[0173] Sample preparation: The coating materials of Example 1, Example 2 and Example 3 were prepared according to the prescribed process, and were evenly coated on the surface of a standard wind turbine blade to complete the curing and drying process.
[0174] Group design: Each coating is tested at least three times to ensure the reliability of the experimental results. Before each test, the coating samples need to be cleaned and pre-treated to ensure the accuracy of the test.
[0175] Environmental control: The experimental environment temperature is strictly controlled at 20℃±2℃, and the humidity is controlled at 50%±5%.
[0176] 6. Experimental results and data presentation
[0177] (1) Ice and snow adhesion test results
[0178] Example No. Average adhesion (N) Maximum adhesion (N) Ice peeling force (N) Example 1 3.0 4.0 2.5 Example 2 2.5 3.5 2.0 Example 3 2.0 2.8 1.5
[0179] Analysis: Example 3 has the smallest adhesion and the highest ice peeling force, showing the best anti-icing performance.
[0180] (2) Salt spray corrosion test results
[0181] Example No. Corrosion damage area (%) Coating integrity (%) Corrosion rate (μm / day) Example 1 15 85 0.32 Example 2 10 90 0.26 Example 3 5 95 0.15
[0182] Analysis: Example 3 performs best in corrosion resistance, has minimal corrosion damage, has the highest coating integrity, and has the lowest corrosion rate.
[0183] (3) Wear resistance test results
[0184]
[0185]
[0186] Analysis: The coating of Example 3 performs best in terms of wear resistance, with the smallest wear depth and the smallest hardness change, indicating that it maintains high durability in long-term mechanical friction.
[0187] (4) Thermal stability test results
[0188] Example No. Maximum thermal weight loss temperature (℃) Thermal weight loss (%) Thermal stability evaluation Example 1 400 8 good Example 2 410 6 excellent Example 3 420 5 Excellent
[0189] Analysis: The coating of Example 3 has the strongest thermal stability, the smallest thermal weight loss, and can work stably at higher temperatures.
[0190] (5) Mechanical fatigue test results
[0191]
[0192] Analysis: The coating of Example 3 exhibits the best mechanical fatigue performance, with the latest appearance of fatigue cracks and the longest fatigue life.
[0193] 7. Experimental Summary
[0194] According to the experimental results, Example 3 showed the best performance in all test items, which is specifically summarized as follows:
[0195] Anti-icing performance: The coating of Example 3 exhibits the smallest ice and snow adhesion and the highest ice peeling force, and has excellent anti-icing ability.
[0196] Corrosion resistance: The coating of Example 3 performed best in the salt spray corrosion test, with extremely low corrosion damage and corrosion rate, and is suitable for high humidity and high salt environments.
[0197] Wear resistance: The coating of Example 3 has the strongest wear resistance, the smallest surface wear, and better resistance to wind and sand and mechanical friction.
[0198] Thermal stability: Example 3 has the best thermal stability and can maintain excellent performance in a high temperature environment and adapt to extreme temperature changes.
[0199] Mechanical fatigue performance: The coating of Example 3 can still maintain integrity under long-term mechanical load and has an extremely long fatigue life.
[0200] In summary, the coating of Example 3 showed the best performance in all test items and is the most suitable anti-icing wind turbine blade coating for use in high-cold and harsh environments.
[0201] Comparative experimental design: Performance comparison between the coating technology of the present invention and the prior art
[0202] Purpose:
[0203] This experiment aims to verify the advantages of the coating technology provided by the present invention over the existing technology in terms of anti-icing, anti-corrosion, wear resistance, etc. Through comparative experiments, it is proved that the technical solution of the present invention has obvious innovation, especially in adapting to the application advantages in the complex environment of high-cold areas.
[0204] Experimental background:
[0205] In high-cold areas, wind turbine blades are exposed to harsh environments such as ice and snow, salt spray corrosion, and sandstorms for a long time. Therefore, the wind turbine blade coating needs to have multiple properties, such as anti-icing, anti-corrosion, and wear resistance. Most coating schemes in the prior art focus on either anti-icing effects or corrosion resistance, and the overall performance of the coating is relatively weak. This experiment will verify the advantages of the multifunctional coating technology of the present invention by comparing the differences in these properties between the prior art coating and the coating of the present invention.
[0206] Comparative experimental design:
[0207] This experiment will use the following comparison scheme:
[0208] Comparative coating 1 (prior art A): adopts traditional anti-icing coating technology, mainly composed of components such as polyurethane and fluoride, focusing on anti-icing effect, but has weak corrosion resistance and wear resistance.
[0209] Comparative coating 2 (prior art B): A coating made of ceramic-based composite materials, which has strong wear resistance, but lacks multifunctional materials such as shape memory alloys and thermally responsive polymers, and has poor anti-icing and anti-corrosion properties.
[0210] Comparative coating 3 (coating of the present invention): It adopts a combination of various innovative materials such as ceramic-based composite materials, shape memory alloy particles, thermal responsive polymers, photocatalysts, super-hydrophobic nanoparticles, etc., and has comprehensive properties such as anti-icing, anti-corrosion, and wear resistance.
[0211] Experimental steps:
[0212] Coating preparation:
[0213] Using the preparation process of the present invention (see steps S1-S6 in the patent scheme) as a benchmark, Example 3 (the coating of the present invention) was prepared.
[0214] The coatings of prior art A and prior art B were prepared according to the processes reported in the literature.
[0215] Each coating is dried after preparation to ensure that the surface is smooth and free of impurities.
[0216] Ice and snow adhesion test:
[0217] At -20℃, the ice and snow adhesion of the three coatings was tested using an ice adhesion tester.
[0218] The adhesion value (unit: N) was recorded. Each coating was tested 3 times and the average value was taken.
[0219] Corrosion resistance test:
[0220] The coating samples were placed in a salt spray corrosion chamber and subjected to a 48-hour salt spray corrosion test in accordance with ASTM B117.
[0221] Observe the corrosion degree of each coating and record the corrosion conditions (such as corrosion spots, color changes, etc.).
[0222] Wear resistance test:
[0223] The test was carried out using a friction and wear testing machine to simulate the environment of wind, sand and mechanical friction.
[0224] The wear volume of each coating was measured after the test, and the area of wear damage was recorded (unit: mm 2 ).
[0225] Thermal stability test:
[0226] The thermal stability of the coating was tested in the temperature range of 100°C-200°C.
[0227] The thermal stability of the coating is determined by the changes in its mass and surface state, and the mass loss rate of the coating is recorded.
[0228] Experimental design:
[0229] The comparative experimental design of the experiment includes the following key factors:
[0230] Each coating sample had uniform surface area, identical dimensions, and was tested under consistent conditions.
[0231] Each test was repeated at least 3 times and the average value was taken to ensure the reliability of the experimental results.
[0232] All tests are carried out in a standard experimental environment to avoid interference from the external environment.
[0233] Experimental results:
[0234]
[0235] Result analysis:
[0236] Ice and snow adhesion:
[0237] The ice and snow adhesion of prior art A is 6.5N, which is relatively high, indicating that the anti-icing performance is poor.
[0238] The adhesion of prior art B is 5.0N, which is better, but still lower than the coating of the present invention.
[0239] The adhesion of the coating of the present invention is 3.5N, which is significantly lower than the other two, indicating that it has excellent anti-icing effect.
[0240] Corrosion resistance:
[0241] Prior art A showed moderate corrosion in the salt spray corrosion test, and the coating showed obvious corrosion.
[0242] The corrosion degree of prior art B is relatively light, but corrosion marks are still visible.
[0243] The coating of the present invention has no corrosion in the salt spray corrosion test, showing extremely strong corrosion resistance.
[0244] Wear resistance:
[0245] The coating wear amount of prior art A is the largest, indicating that the wear resistance is poor.
[0246] The wear amount of the prior art B is smaller, but not as good as the coating of the present invention.
[0247] The coating of the present invention has minimal wear and exhibits excellent wear resistance.
[0248] Thermal stability:
[0249] The prior art A has poor thermal stability and high mass loss rate.
[0250] The thermal stability of prior art B is better, but still inferior to that of the coating of the present invention.
[0251] The mass loss rate of the coating of the present invention is only 3%, showing excellent thermal stability.
[0252] Experimental summary:
[0253] Anti-icing performance: Compared with the existing technologies A and B, the coating of the present invention has the lowest ice and snow adhesion and the best anti-icing effect. It can effectively reduce the adhesion of ice and snow, thereby improving the operating stability of wind turbine blades in cold environments.
[0254] Corrosion resistance: The coatings of prior art A and B both show a certain degree of corrosion, especially the prior art A, which has a more serious degree of corrosion. However, the coating of the present invention is corrosion-free, exhibits excellent corrosion resistance, and is suitable for high salt spray environment.
[0255] Wear resistance: The wear amount of the coating of the present invention is significantly lower than that of the prior art A and B, and it can withstand greater wind and sand and mechanical friction, and is suitable for long-term use in harsh environments.
[0256] Thermal stability: The thermal stability of the coating of the present invention is significantly better than that of the prior art and can maintain good performance in a high temperature environment.
[0257] In summary, the coating technology of the present invention shows obvious advantages in anti-icing, anti-corrosion, wear resistance and thermal stability. Compared with the existing technology, it has significant innovation and is suitable for wide application in anti-icing technology of wind turbine blades in high-cold and high-corrosion environments.
[0258] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A wind turbine blade coating suitable for anti-icing in high-cold areas, characterized in that: By weight percentage, it includes the following components: 45-55% ceramic matrix composites, which include aluminum oxide, silicon nitride and silicon carbide; 5-10% shape memory alloy particles; 2-5% thermoresponsive polymer; 3-7% photocatalyst titanium dioxide; 5-8% superhydrophobic nanoparticles; 10-15% antioxidant enhancer; 5-8% fluoride composites; 10-15% solvents and thinners.
2. The anti-icing wind turbine blade coating suitable for high-cold areas according to claim 1 is characterized in that: The shape memory alloy particles are optionally one of nickel-titanium alloy and copper-based shape memory alloy, and the thermal responsive polymer is a polymer shape memory polymer.
3. The anti-icing wind turbine blade coating suitable for high-cold areas according to claim 1 is characterized in that: The super hydrophobic nanoparticles are selected from one of silicon fluoride nanoparticles and carbon fluoride nanoparticles, and the antioxidant enhancer is selected from one of titanium alloy particles and aluminum alloy particles.
4. The anti-icing wind turbine blade coating suitable for high-cold areas according to claim 1 is characterized in that: The fluoride composite material is selected from one of aluminum fluoride and sodium fluoride, and the solvent and diluent is selected from one of ethanol, isopropanol, xylene and ammonium acetate.
5. The anti-icing wind turbine blade coating suitable for high-cold areas according to claim 1 is characterized in that: The particle size of the ceramic-based composite material is in the range of 1-10 μm, and the mixing ratio of the ceramic-based composite material is alumina: Silicon nitride:silicon carbide=3:2:
1.
6. The anti-icing wind turbine blade coating suitable for high-cold areas according to claim 1 is characterized in that: The particle size of the shape memory alloy particles is in the range of 20-50 μm, the particle size of the super hydrophobic nanoparticles is in the range of 10-100 nm, and the particle size of the antioxidant enhancer is in the range of 10-50 μm.
7. A coating process for wind turbine blades to prevent ice buildup in cold regions, characterized in that: The method for preparing a component material for an anti-icing wind turbine blade coating suitable for high-cold areas according to any one of claims 1 to 6 comprises the following steps: S1. Material preparation: preparing the component materials according to the above weight percentage, including ceramic-based composite materials, shape memory alloy particles, thermal responsive polymers, photocatalysts, super-hydrophobic nanoparticles, antioxidant enhancers, fluoride composite materials and solvents; S2. Material mixing and homogenization: The above components are put into a mixing container according to a predetermined ratio, and are preliminarily mixed by a biaxial high-speed stirrer, with the stirring speed set to 500-800 rpm for 15 min. Thereafter, they are further mixed by a ball mill, and wet ball milling is performed using isopropanol or ethanol as a solvent; S3, solvent addition: adding solvent and diluent according to the required viscosity requirements of the coating liquid; S4, coating operation: using a spraying device, the coating liquid uniformly mixed in the above steps is evenly coated on the surface of the fan blade; S5. Curing and drying: Perform preliminary curing at 40°C-80°C for 10-20 minutes, then raise the temperature to 120°C for 20-40 minutes of high temperature curing, and finally allow the coating to cool naturally at room temperature; S6. Surface treatment: Use corona treatment technology to enhance the coating surface, the power is set to 2-4kV, the treatment time is 1-2min, and the surface is scanned by laser beam, the laser power is set to 50-150W, and the scanning speed is 5-10mm / s.
8. The anti-icing wind turbine blade coating process suitable for high-cold areas according to claim 7 is characterized in that: The viscosity of the coating liquid in step S3 is in the range of 50-100 cP.
9. The anti-icing wind turbine blade coating process suitable for high-cold areas according to claim 7 is characterized in that: When the coating operation in step S4 is performed by spraying, the spraying pressure of the spraying equipment is 0.2-0.5 MPa, and the spraying distance is controlled within the range of 10-15 cm.
Citation Information
Cited By
Coating and electrical equipment
CN120842980A